Leadership models in a modern organizations - Dasmadi Dasmadi (Enrichment : Journal of Management, 2023)
This very simple study will discuss the concept of transformational leadership which is a leadership style that can turn the vision and mission into action, transforming individuals to want to change towards improving their quality. In its implementation, there are several factors that influence it, namely idealiazed influence, inspirational motivation, individual consideration, and intellectual stimulation. The purpose of writing to explain in a comprehensive manner about the concept of leadership, transformational leadership style, and characteristics of transformational leadership. Organizations or corporation need leaders to advance, develop and bring the institutions they lead to a better direction. Transformational leadership is one of the modern leadership styles that is able to change from vision and mission to action and is done by creating a clear vision, motivating staff to be creative, innovative, building a learning culture, and building effective communication. Constructive criticism and suggestions from readers are highly expected for the perfection of this study.